2013
DOI: 10.1177/0269881113515062
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in daytime sleepiness with clarithromycin in patients with GABA-related hypersomnia: Clinical experience

Abstract: The macrolide antibiotic clarithromycin can enhance central nervous system excitability, possibly by antagonism of GABA-A receptors. Enhancement of GABA signaling has recently been demonstrated in a significant proportion of patients with central nervous system hypersomnias, so we sought to determine whether clarithromycin might provide symptomatic benefit in these patients. We performed a retrospective review of all patients treated with clarithromycin for hypersomnia, in whom cerebrospinal fluid enhanced GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 34 publications
2
38
1
Order By: Relevance
“…The same group has also studied the macrolide antibiotic clarithromycin in enhancing vigilance in hypersomnia patients, presumably via pharmacological antagonism of GABA-A receptors. A retrospective review of clarithromycin treatment in 53 patients with this GABA-related hypersomnia showed 64 % reported improvement in daytime sleepiness [84]. These findings suggest that GABA may play a role in the promotion of sleep in pathological hypersomnia.…”
Section: Neurological Disorders Of Sleep and Sleep-promoting Systemsmentioning
confidence: 95%
“…The same group has also studied the macrolide antibiotic clarithromycin in enhancing vigilance in hypersomnia patients, presumably via pharmacological antagonism of GABA-A receptors. A retrospective review of clarithromycin treatment in 53 patients with this GABA-related hypersomnia showed 64 % reported improvement in daytime sleepiness [84]. These findings suggest that GABA may play a role in the promotion of sleep in pathological hypersomnia.…”
Section: Neurological Disorders Of Sleep and Sleep-promoting Systemsmentioning
confidence: 95%
“…13 Building on these findings, clarithromycin is being tested as a potential treatment for hypersomnia, and improvement in daytime sleepiness has been reported in initial clinical studies for patients on clarithromycin 500 mg twice per day vs placebo. 5,6 These results were of particular interest to us because of our long-standing research interests in understanding the mechanisms underlying Parkinson's disease (PD) and our extensive work managing patients with PD. Axial motor impairments represent a significant cause of disability in PD, which is mainly explained by lack of efficacy of dopaminergic treatments on these symptoms.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…Therefore, orally administered negative allosteric moderators/antagonists of GABA A receptors have been explored as alternative treatments. 5,6 Clarithromycin ( Figure 2), a macrolide antibiotic approved in both oral and intravenous forms, has a range of neurotoxic side effects, including excitation, mania, psychosis, insomnia, and nonconvulsive status epilepticus. 7−10 Although the mechanism of action underlying these CNS side effects is unknown, 7 clarithromycin is purported to be a negative allosteric modulator of GABA A receptors from in vitro wholecell patch clamp experiments, albeit with low affinity (18% and 45% inhibition at 3 and ∼300 μM, respectively).…”
Section: * S Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fi ndings that hypersomnolent patients demonstrate a positive allosteric modulator of GABA A receptors in their CSF, 9 and that clarithromycin is a negative allosteric modulator of GABA A receptors, 127 Trotti et al 128 reported the clinical use of clarithromycin in 53 subjects with central hypersomnolence disorders (without cataplexy). Sixty-four percent of these subjects, who had failed an average of 2.6 prior wake-promoting medications, reported improved EDS.…”
Section: Treatmentmentioning
confidence: 99%